2016
DOI: 10.1136/injuryprev-2015-041707
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic injuries in Baghdad from 2003 to 2014: results of a randomised household cluster survey

Abstract: IntroductionAround 50 million people are killed or left disabled on the world's roads each year; most are in middle-income cities. In addition to this background risk, Baghdad has been plagued by decades of insecurity that undermine injury prevention strategies. This study aimed to determine death and disability and household consequences of road traffic injuries (RTIs) in postinvasion Baghdad.MethodsA two-stage, cluster-randomised, community-based household survey was performed in May 2014 to determine the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In 2015 the rate was 20/100,000, 31 with 60% of the survivors developing permanent disabilities that in turn affected their living and socioeconomic status. 32 A study in Iraq in 2013 revealed a RTA fatality rate of 8.6 to 10.7 per 100,000, of whom 78.2 % were males and 28.5 % were children. 29…”
Section: Resultsmentioning
confidence: 99%
“…In 2015 the rate was 20/100,000, 31 with 60% of the survivors developing permanent disabilities that in turn affected their living and socioeconomic status. 32 A study in Iraq in 2013 revealed a RTA fatality rate of 8.6 to 10.7 per 100,000, of whom 78.2 % were males and 28.5 % were children. 29…”
Section: Resultsmentioning
confidence: 99%
“…The 2016 global EM articles selected for full review are listed in Table 4. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Nineteen articles were selected for inclusion, of which 15 (79%) were categorized as emergency care, three (16%) were categorized as development, and one (5%) was categorized as disaster response articles. Eighteen (95%) articles were original research manuscripts and one (5%) was a review article.…”
Section: Resultsmentioning
confidence: 99%
“…High-scoring articles this year described barriers to emergency medical services use in India, 31 the significant increase in road traffic accidents and injuries in postinvasion Iraq, 29 and the limited implementation of the World Health Organization's trauma guidelines. 21 In terms of trauma care, a study by Chattopadhyay et al 19 found that a novel and low-cost dressing performed as well as Xeroform in vitro and in vivo for management of burn wounds, providing a new option for practitioners in resource-limited environments who manage victims of trauma and burns.…”
Section: Plos Onementioning
confidence: 99%
“…In addition, earlier endeavors have mentioned Bangladesh as a low middle-income country and the pedestrians are at high risk of getting involved in RTA. [ 33 34 35 ] Some studies have identified motorcyclists are at high risk of getting involved in RTA;[ 10 11 15 36 37 ] perhaps, the situation is similar in Bangladesh. However unfortunately, the knowledge and awareness about traffic rules among the motorcyclists are very poor in Bangladesh and the commercial vehicle drivers are in the second position of the row.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing various literature from different countries, it significantly showed that in developing countries, people in the age group of 15–44 years, especially the males are carrying out a greater share of the burden of RTA across different times. [ 10 11 12 13 ] The motorcycle is the most vulnerable vehicle along with bus and truck, and pedestrians and passengers are the main sufferers[ 14 15 ] in RTA. Various studies have previously demonstrated that there are many reasons that affect RTA, such as violating traffic laws and signals, novice drivers, excessive speed, faulty road and management, and lack of knowledge.…”
Section: Introductionmentioning
confidence: 99%